Metabolic engineering of Methanosarcina acetivorans for lactate production from methane. Issue 4 (11th November 2016) - McAnulty, Michael J.; Poosarla, Venkata Giridhar; Li, Jine; Soo, Valerie W. C.; Zhu, Fayin; Wood, Thomas K.
ABSTRACT: We previously demonstrated anaerobic conversion of the greenhouse gas methane into acetate using an engineered archaeon that produces methyl‐coenzyme M reductase (Mcr) from unculturable microorganisms from a microbial mat in the Black Sea to create the first culturable prokaryote that reverses methanogenesis and grows anaerobically on methane. In this work, we further engineered the same host with the goal of converting methane into butanol. Instead, we discovered a process for converting methane to a secreted valuable product, L ‐lactate, with sufficient optical purity for synthesizing the biodegradable plastic poly‐lactic acid. We determined that the 3‐hydroxybutyryl‐CoA dehydrogenase (Hbd) from Clostridium acetobutylicum is responsible for lactate production. This work demonstrates the first metabolic engineering of a methanogen with a synthetic pathway; in effect, we produce a novel product (lactate) from a novel substrate (methane) by cloning the three genes for Mcr and one for Hbd. We further demonstrate the utility of anaerobic methane conversion with an increased lactate yield compared to aerobic methane conversion to lactate. Biotechnol. Bioeng. 2017;114: 852–861. © 2016 Wiley Periodicals, Inc. Abstract : The authors previously reversed methanogenesis for the first time to grow anaerobically on methane by producing active methyl‐coenzyme M reductase from an unculturable organism in the Black Sea in the methanogen Methanosarcina acetivorans . Here, further metabolic engineering by adding production of 3‐hydroxybutyryl‐CoA dehydrogenase from Clostridium acetobutylicum led to the production of optically pure L ‐lactate from methane with a higher yield than that of aerobic processes.